Study of key technology for reconfigurable satellite platform supporting network interconnection - Chao WANG; Xiao-dong HAN; Rui WANG; Xi ZHOU; Lin-lu YANG; Ya-ping LIU (Tongxin xuebao)
Reconfigurable satellite platform is a new spacecraft design concept.The application of distributed computing in reconfigurable integrated satellite platform was studied,the standard mechanical interface,electrical interface for the separation or separation between main platform and a variety of payloads to form a new combination and achieve the expansion of platform functions and efficient use was proposed.Including the security control protocol,scalable design,distributed computing and management models and other aspects of a detailed design,the key technologies of reconfigurable integrated satellite platforms supporting network interconnection were studied to meet the existing communications,remote sensing and navigation satellites’ needs.It will be promoted for the spacecraft design to the integrated business and in the orbit reconfiguration direction of continuous development,which will enhance the stability of the orbit operation,survivability and maintainability and provide a reliable technical foundation for the world of integrated network research.